Spiroplasma Symbiont of the Pea Aphid, Acyrthosiphon pisum (Insecta: Homoptera) - Fukatsu, Takema (American Society for Microbiology, 2001)
From a laboratory strain of the pea aphid, Acyrthosiphon pisum, we discovered a previously unknown facultative endosymbiotic bacterium. Molecular phylogenetic analysis based on 16S ribosomal DNA revealed that the bacterium is a member of the genus Spiroplasma. The Spiroplasma organism showed stable vertical transmission through successive generations of the host. Injection of hemolymph from infected insects into uninfected insects established a stable infection in the recipients. The Spiroplasma symbiont exhibited negative effects on growth, reproduction, and longevity of the host, particularly in older adults. Of 58 clonal strains of A. pisum established from natural populations in central Japan, 4 strains possessed the Spiroplasma organism.